1977
DOI: 10.1136/hrt.39.11.1239
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular performance in patients with left ventricular hypertrophy caused by systemic arterial hypertension.

Abstract: There is considerable controversy concerning myocardial performance in hypertrophied states. Data derived from in vitro and in vivo experiments as well as available information in human studies suggest that ventricular function is depressed as a result of hypertrophy (Spann et al., 1967(Spann et al., , 1969Bing et al., 1971;Frohlich et al., 1971;Spann et al., 1972;Gunning et al., 1973;Alpert et al., 1974;Mehmel et al., 1975). However, more recent animal experiments suggest that performance is normal in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

1978
1978
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…These data are consistent with the result of a previous study (Karliner et al, 1977) which showed that hypertensive patients who were under antihypertensive therapy demonstrated normal left ventricular function.…”
Section: Discussionsupporting
confidence: 95%
“…These data are consistent with the result of a previous study (Karliner et al, 1977) which showed that hypertensive patients who were under antihypertensive therapy demonstrated normal left ventricular function.…”
Section: Discussionsupporting
confidence: 95%
“…It appears that the ejection fraction is maintained in the normal range in aortic stenosis for a long time. A similar finding was reported for patients with arterial hypertension (18).…”
Section: Discussionsupporting
confidence: 79%
“…The methods and recording and analyzing techniques have been described earlier "~1 4 The BP was measured in four different situations:…”
Section: Study Protocolmentioning
confidence: 99%
“…14 The ratio between resting laboratory diastolic BP and isovolumetric contraction time (DBP/ ICT) was calculated as a measure of isovolumetnc pressure nse velocity ' 4 Because LV ejection time is influenced by heart rate, this interval also was expressed as a percentage of the expected value at the observed heart rate with the regression equation: LV ejection time = 390 -1.51 x heart rate, which was previously obtained from a control group of middleaged normotensive men.…”
Section: Imentioning
confidence: 99%